2007
DOI: 10.1080/09273970701669983
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Severity of and Recovery from Anisometropic Amblyopia

Abstract: This study demonstrates the difficulty of developing a guideline for screening and treatment of anisometropia. Even though there seems to be a correlation between type and degree of anisometropia in a majority of patients, there is also a significant number of cases that do not follow this pattern. Another important observation is the presence of binocular vision at the first evaluation as a good prognostic indicator for visual recovery with optical correction alone, even without penalization therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
(19 reference statements)
2
26
0
1
Order By: Relevance
“…One more idea about good prognosis is the finding of binocular vision at first screening it improves visual recovery with the change in shape of optical fibers without changing treatment plan. 12 The results of our study are valid for distribution type of anisometropic amblyopia in different age groups as our data supports that age groups 11-15, 16-20, 21-25 have relatively less severity of anisometropic amblyopia as compared to the age group 25-30. Our data also supports the previous studies that younger children have more potential of stereopsis than adults.…”
Section: Outsupporting
confidence: 83%
“…One more idea about good prognosis is the finding of binocular vision at first screening it improves visual recovery with the change in shape of optical fibers without changing treatment plan. 12 The results of our study are valid for distribution type of anisometropic amblyopia in different age groups as our data supports that age groups 11-15, 16-20, 21-25 have relatively less severity of anisometropic amblyopia as compared to the age group 25-30. Our data also supports the previous studies that younger children have more potential of stereopsis than adults.…”
Section: Outsupporting
confidence: 83%
“…1,2 Anisometropia as the most frequent cause of amblyopia has been evaluated in numerous studies. [3][4][5] However, anisometropia associated with high myopia has often been excluded from those studies. The few studies investigating anisometropic amblyopia caused by unilateral high myopia have concluded that this type of amblyopia had poorer treatment outcomes.…”
mentioning
confidence: 99%
“…12 Occlusion therapy and atropine further improved the outcome when refractive correction alone was not satisfactory. 13,14 Several studies have reported that binocular function can be improved with improvement of visual acuity [15][16][17] ; however, most of these were retrospective studies, [17][18][19] and they included a variety of patients including those with strabismus. [15][16][17] This study aimed to evaluate the degree of improvement of binocular function among previously untreated anisometropic children and to identify the factors that affect the degree of improvement.…”
mentioning
confidence: 99%